Correlation between antioxidant and physicochemical parameters of honey samples from Bosnia and Herzegovina and Turkey - Samardžić, Melinda; Ibragić, Saida (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2022)
The aim of this study was to determine the association value between the following parameters and the antioxidant properties of honey: colour, phenolics content (TPC), flavonoid content (TFC), proline and ascorbic acid content. The samples were collected in Bosnia and Herzegovina and Turkey and included honeydew, monofloral and polyfloral honey. The antioxidant activity of honey samples was determined using the ABTS and DPPH assays. Based on the correlation matrix, the main findings revealed a strong correlation between antioxidant activity and TPC, TFC, proline content and colour. Honey colour was in best correlation with the TFC (r = 0.910, p < 0.001) where dark coloured honeys showed a higher TFC, however antioxidant activity showed a highly significant dependence on theTPC (DPPH-TPC: r = - 0.872; ABTS-TPC: r = - 0.783, p < 0.001). Ascorbic acid was not established as a predictive parameter that can be used to estimate the antioxidant properties of honey and did not significantly correlate with any of the remaining variables.